(3HQfGeL GcSd (B2000 (3hJWHjbGJgG GdeMGSHIs - (3UdGM GdOjf YHO GdefYe(B, (3eHGQcs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3bSe gPG GdcJGH Edi SJI aUhd NUU GdChd efgG dYQV CSGSjGJ HQfGeL (BEXCEL 2000 .(3hJfGhd GdaUd GdKGfj GdUjZ hGdOhGd aj HQfGeL GcSd (B2000 (3CeG GdaUd dKGdK aYQV dehVhY bhGYO GdHjGfGJ HWQjbI eJYebI hJMdjdjI eY GeKdI hJWHjbGJ eMGSHI edGFeI aj gPG GdeLGd , CeG GdaUd GdQGHY hGdNGeS abO JfGhdJ ajgG ehVhY GdJNWjWGJ GdHjGfjI hJMdjd (B"(3eGPG dh(B" (3hJWHjbGJgN GdMGdjI hGNJJe gPG GdeQLY HCge echfGJg aj GdaUd GdSGOS hgh YQV deLehYI ef GdJWHjbGJ GdeMGSHjI GdeJfhYI hHjGf OhQ GdeMGSH ef NdGd HQfGeL GcSd (B2000 (3aj eYGdLI eKd gPg GdJWHjbGJ (B.s
Keywords: (3GcSd (B2000s; (3GdeLOhds